MATHEMATICAL CONNECTION OF GEOMETRY PROBLEMS BASED ON NUMERACY LITERACY THROUGH THE POLYA FRAMEWORK - Ajeng Gelora Mastuti; Syafruddin Kaliky; Aliati Siolimbona; Jiran Rano (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2023)
The results of the 2018 Program for International Student Assessment (PISA) study released by The Organization for Economic Cooperation and Development (OECD) show that the numeracy literacy skills of Indonesian students are at a low level, namely getting a score of 379 out of the OECD average score of 487 (OECD, 2019). As a result, students tend not to be able to solve problems correctly, and the cause is a need for mathematical connection skills. This study aims to describe the mathematical connections based on numeracy literacy in geometry. This research is a qualitative descriptive study. The participants in this study were 38 grade 7 students from 3 different Madrasas in Maluku. Two students will take the research subjects from saturated data after being given a numeracy literacy-based test. In this study, students were asked to state the results of their thoughts on solving geometry concept problems given orally. Analyzing the research data was carried out through three stages: data reduction, data presentation, and drawing conclusions. The findings in this study of mathematical connections within the Polya framework can be divided into two: structured analytics and unstructured analytics.